Delphi path simulator for unveiling development opportunities in the forest industries by contrasting forest management practices : the case of North Karelia - Lehtonen, Olli; Tykkyläinen, Markku (Elsevier, 2014)
This paper investigates how uneven-aged forest management practice could supply roundwood under different demand conditions in North Karelia in Finland. Four alternative development paths for the forest industries were estimated by means of the Delphi method combining past development in forest industries with expert visions of industrial restructuring and future final demand. The results of a single-tree forest simulator were used to indicate local opportunities for the supply of roundwood, and the demand for roundwood was estimated via the resource matrix of the input–output model for each alternative development path. The study reveals that both even-aged and uneven-aged forest management would be technically possible in order to satisfy the mills' demand for wood in the tested instances. Further research is recommended to compare the profitability of alternative production technology chains and to carry out a geospatial supply and demand analysis for wood, which would fine-tune the results locally.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; simulation; Delphi; forest industry; forest management practices; Pohjois-Karjala; simulointimallit; metsänhoito; forest management; simulation models